KREATIVITAS GURU AGAMA KATOLIK DALAM MEWUJUDKAN PEMBELAJARAN YANG FLEKSIBEL DAN INOVATIF DI SMP NEGERI 1 SEKOLAQ DARAT - Kesin, Kesin; Dole, Donatus; Yuda, Yohanes (Lembaga Penelitian STKIP Widya Yuwana, 2025)
This study aims to describe the creativity of Catholic Religion teachers in realizing flexible and innovative learning at SMP Negeri 1 Sekolaq Darat. This study uses a descriptive qualitative approach with data collection techniques in the form of interviews, observations, and documentation. The results of the study indicate that teachers apply flexibility through language adjustments, simplifying teaching materials, and selecting methods that are appropriate to student characteristics, such as discussions, questions and answers, and reflections. Innovation is shown through the use of simple media such as images, religious videos, and student worksheets that are contextual and thought-provoking. Despite facing various limitations such as minimal technological facilities and a small number of Catholic students, teachers continue to show of a strong commitment and initiative in creating meaningful and valuable learning. These findings confirm that teacher creativity is an important factor in building a religious learning process that is relevant, reflective, and touches students' lives in real terms.